Major variation in hepatocellular carcinoma treatment and outcomes in England: a retrospective cohort study. Issue 1 (9th May 2022) - Beecroft, Sue; O'Connell, Matthew; Nassar, Ayman; Noon, Katie; Pollock, Kevin G; Palmer, Dan; Cross, Timothy J S
Abstract : Objective: Hepatocellular carcinoma (HCC) is increasingly incident in England, while survival remains poor with regional disparities. We aimed to explore the differences in HCC treatment across different geographical regions and to examine the impact on cancer survival. Methods: Incident HCC cases and treatment were identified from the English Hospital Episode Statistics (2016–2017) and then a subset by National Health Service (NHS) regions. Treatment was grouped into curative, palliative and untreated. Median survival was estimated to date of death in the national statistics. Results: The median observed survival was 8.6 months (95% CI 7.5 to 9.9) across all 2160 HCC cases, 52.1 months (CI 50.5, not reached) in 449 (20.8%) treated with curative intent, 21.0 months (CI 18.5 to 24.5) after other cancer-specific treatment in 449 (20.8%), and 2.3 months (CI 2.1 to 2.6) in 1262 (58.4%) untreated. Across NHS regions, <50% of cases received treatment (30.4%–49.6%), while between 14.2% and 27.7% had curative treatment. The 3-year survival was similar (23.5%–29.7%), except in the London region (40.0%). Conclusion: Majority of HCC cases in England are untreated and survival remains low, with variation in outcomes in regions with similar incident rates. A deeper exploration of regional treatments and screening practice is required to improve early detection and survival.